Pengaruh Debt to Equity Ratio (DER) dan Current Ratio (CR) Terhadap Return on Asset (ROA) pada Perusahaan Subsektor Logistik dan Pengiriman yang Terdaftar di Bursa Efek Indonesia Periode 2021-2024 - Rahmawati; Siti Rusidah; Hairudinor; Novia Nour Halisa (Smart Business Journal (SBJ), 2026)
The objective of this study is to examine the impact of the Debt-to-Equity Ratio (DER) and the Current Ratio (CR) on Return on Assets (ROA) for companies in the logistics and shipping subsectors listed on the Indonesia Stock Exchange during the 2021–2024 period. Multiple linear regression analysis is the quantitative tool of choice in this investigation. There are a total of 25 firms that make up the population, all of which are registered on the Indonesia Stock Exchange and are involved in logistics and shipping. Over a four-year observation period, nine firms met the criteria for the sample, which yielded thirty-six data units for the purposive sampling. From what we can see, ROA is somewhat affected by the Debt-to-Equity Ratio (DER), which has a negative but insignificant influence, and by the Current Ratio (CR), which has a positive but insignificant effect. In addition, for the years 2021–2024, the Return on Assets (ROA) of logistics and shipping subsector businesses listed on the Indonesia Stock Exchange is affected—albeit marginally—by the Debt-to-Equity Ratio (DER) and the Current Ratio (CR).